PENGARUH INOVASI PRODUK TERHADAP MINAT BELI SMARTPHONE DENGAN CONSUMER INNOVATIVENESS SEBAGAI VARIABLE MODERASI - Hans Fanolo Kristian Daeli (DIGEST MARKETING, 2018)
The aim of this research is to examine the influence of product innovation on purchasing intention where consumer innovativeness considered as moderator variable. Sample is Chinese smartphones users in Jambi. The research results showed that product innovation on purchasing intention that moderated by consumer innovativeness is significantly related. Hence, product innovation allowed by corporate effort to enlighten consumer about technologies content to every product delivered.